Malaysia attempts in reduce carbon dioxide (CO2) emission and sequestration in bio-concrete system; a future direction - Alshalif, A Faisal; Irwan, JM; Othman, N.; Al-Gheethi, AA (Penerbit UTHM, 2020)
In Malaysia, upbringing the production of mussel is one of the most second important aquaculture The greenhouse gasses increase in this century especially carbon dioxide (CO2) compare to the previous centuries due to the increase of anthropogenic activities in all countries around the world [1][2][3]. The high concentration CO2 in the atmospheric cause a catastrophic environmental issues such as; global warming, change in rainfall, rise of sea level and climatic changes..